Is the femoral intramedullary alignment already actual in total knee arthroplasty? - Andrea Tecame; Andrea Gambineri; Pierangelo Za; Paolo Adravanti (Journal of Experimental Orthopaedics, 2023)
Abstract Clinical outcomes and overall alignment after total knee arthroplasty (TKA) depend on femoral component positioning in the sagittal and the coronal plane, making choice of the distal femoral cutting guide crucial. Currently, there is no consensus on the potential advantage of an extramedullary (EM) guide compared to an intramedullary (IM) guide in TKA. The IM guide is the most widely used system for making the distal femoral cut although evidence for its superiority over the EM guide is lacking. However, inaccuracies arising with the IM guide include location of the rod entry point in the coronal plane, femoral canal diameter, femoral bowing, and structural features of the rod. Furthermore, the invasive procedure is associated with increased risk of postoperative blood loss, thromboembolic complications, and intraoperative fractures. While the EM guide has no such difficulties, its accuracy depends on the instruments used. Studies have reported results not inferior to the IM guide and a lower number of postoperative complications. Patient‐specific instrumentation (PSI) and robotic and computer‐assisted TKA have achieved excellent clinical and radiographic results and can overcome the problems inherent to the IM and the EM guide. Authors performed a systematic review of the literature and proposed a narrative review to summarize the characteristics of the IM and the EM guide and compare the advantages and disadvantages of each, as well as their limitations in comparison with new technologies. Authors also expressed their expert opinion.